The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/ejic.201100130
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability of High Performance Thermoelectric β‐Zn4Sb3 in Argon

Abstract: The stability of the high performance thermoelectric β‐Zn4Sb3 is investigated by multi‐temperature high resolution synchrotron powder X‐ray diffraction. Contrary to previous claims β‐Zn4Sb3 is not stable when heated in argon and degradation is observed already at 500 K. Nevertheless, the thermal stability of β‐Zn4Sb3 is much improved in argon (ca. 5 wt.‐% degradation after three heating cycles to 625 K) relative to heating in atmospheric air (ca. 60 wt.‐% degradation). Based on identification of the decomposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…[4] Amongt heses trategies, nanocomposite TE materials, whichare designed to introduce nanometer-sized polycrystallinesa nd interfaces into bulk materials, can be considered as an effective approacht op roduce highperformance TE materials with low cost and large volume. [17,[28][29][30][31][32][33] Therefore, many studies have focused on the stability of Zn 4 Sb 3 under differentc onditions, for example in inert gas, [23,33,34] air, [34] static vacuum, [23] and dynamic vacuum. 5nm-10 mm, typically) grains on am ain matrix that creates extensivei nterfaces between the neighbouring nanoparticles, which allows significantly lower thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Amongt heses trategies, nanocomposite TE materials, whichare designed to introduce nanometer-sized polycrystallinesa nd interfaces into bulk materials, can be considered as an effective approacht op roduce highperformance TE materials with low cost and large volume. [17,[28][29][30][31][32][33] Therefore, many studies have focused on the stability of Zn 4 Sb 3 under differentc onditions, for example in inert gas, [23,33,34] air, [34] static vacuum, [23] and dynamic vacuum. 5nm-10 mm, typically) grains on am ain matrix that creates extensivei nterfaces between the neighbouring nanoparticles, which allows significantly lower thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…[3] [7] [8] Despite its importance, only have a few attempts been made to address the thermal stability issue of thermoelectrics at their elevated working temperature. [9] [10] [11] [12] Zinc antimony is a typical 'phonon glass, electron crystal', one of the best thermoelectrics at moderate temperature. [13] [14] [15]In our previous experiments, it was found that β−Zn 4 Sb 3 samples become metastable around 425 K, but above 565K it recovers its stability.…”
mentioning
confidence: 99%
“…Thermal stability and oxidation of layer-structured rhombohedral In 3 The thermal stability and oxidation of layer-structured rhombohedral In 3 Se 4 nanostructures have been investigated. In-situ synchrotron X-ray diffraction in a sealed system reveals that In 3 Se 4 has good thermal stability up to 900 C. In contrast, In 3 Se 4 has lower thermal stability up to 550 or 200 C when heated in an atmosphere flushed with Ar or in air, respectively.…”
mentioning
confidence: 99%
“…The thermal stability is a measure of the resistance of a material to transformation and/or decomposition at elevated temperatures and is an important intrinsic characteristics of any material. 1 For example, for a given material, having a superior thermal stability is important for high-temperature applications, such as thermoelectric energy conversion, [2][3][4] high-temperature catalytic reactions, 5 and for use in fuel cells. 6 Therefore, extensive investigations have been performed to explore the material thermal stability in bulk or nanoscale forms.…”
mentioning
confidence: 99%
See 1 more Smart Citation